2015
DOI: 10.3747/pdi.2013.00259
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Dna Damage and Mortality in Hemodialysis and Peritoneal Dialysis Patients

Abstract: ♦ Background and Aims: Increased oxidative stress in dialysis patients is thought to contribute to increased mortality; however, confirmatory data are scarce. We analyzed the serum concentration of 8-hydroxy-2′-deoxyguanosine (8-OHdG), a marker of oxidative stress, in relation to mortality in hemodialysis (HD) and peritoneal dialysis (PD) patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 41 publications
2
42
0
2
Order By: Relevance
“…We also used an ELISA to assess 8‐oxo‐2′‐dG in plasma samples, as conventional chromatographic methods do not have the sensitivity to measure plasma levels. Although the circulating levels of 8‐oxo‐2′‐dG detailed in this study are similar to those reported in cross‐sectional studies using ELISA‐based assays in patients with diabetes mellitus25, 26, 27 and other settings,28, 29, 30, 31, 32 it is understood that ELISA overestimates 8‐oxo‐2′‐dG when compared with high‐sensitivity mass spectroscopy 33. This is partly because of the former method including DNA fragments containing 8‐oxo‐2′‐dG, in addition to free 8‐oxo‐2′‐dG, as well as the presence of interfering compounds in plasma.…”
Section: Discussionsupporting
confidence: 82%
“…We also used an ELISA to assess 8‐oxo‐2′‐dG in plasma samples, as conventional chromatographic methods do not have the sensitivity to measure plasma levels. Although the circulating levels of 8‐oxo‐2′‐dG detailed in this study are similar to those reported in cross‐sectional studies using ELISA‐based assays in patients with diabetes mellitus25, 26, 27 and other settings,28, 29, 30, 31, 32 it is understood that ELISA overestimates 8‐oxo‐2′‐dG when compared with high‐sensitivity mass spectroscopy 33. This is partly because of the former method including DNA fragments containing 8‐oxo‐2′‐dG, in addition to free 8‐oxo‐2′‐dG, as well as the presence of interfering compounds in plasma.…”
Section: Discussionsupporting
confidence: 82%
“…Several studies reported the strong association between serum ADMA levels and mortality, as well as CV events in stable HD patients . OS‐mediated DNA damage has also been associated with enhanced atherosclerosis, all‐cause and CV mortality in maintenance HD patients …”
Section: Os and Clinical Endpointsmentioning
confidence: 99%
“…[81][82][83] OS-mediated DNA damage has also been associated with enhanced atherosclerosis, allcause and CV mortality in maintenance HD patients. 84,85 Another study showed that serum levels of ox-LDL antibodies was a strong independent risk predictor of CV mortality in a cohort of 94 stable, HD patients, followed for 4 years. 86 In a cross-sectional, observational, prospective study, 44 HD patients were followed for a long period (9 years) for all-cause and CV mortality.…”
Section: Os and Clinical Endpointsmentioning
confidence: 99%
“…Recently, Xu et al. used multivariable Cox regression models, including 303 hemodialysis and peritoneal dialysis patients adjusted for age, sex, body mass index, dialysis modality, dialysis vintage, and comorbidity score, and found that 8‐hydroxy‐2′‐deoxyguanosine was significantly associated with all‐cause mortality.…”
Section: Oxidative Stress and Outcomementioning
confidence: 99%
“…Nine clinical studies have assessed the relationship between biomarkers of oxidative stress and CVD events, CVD-related mortality, and all-cause mortality in chronic hemodialysis patients (46,(52)(53)(54)(55)(56)(57)(58)(59). Four studies have assessed and demonstrated an association between biomarkers of oxidative stress and the development of new CDV events (51,57,58).…”
Section: Oxidative Stress and Outcomementioning
confidence: 99%